Commerce And Industry: Historical Review 1815 - Australian Chamber of Commerce and Industry ([Barton, Australian Capital Territory] : Australian Chamber of Commerce and Industry, 2007)
Identifying national trends and conditions for the small business sector.
Title from cover.
Also available online. Address as at 11/08/2014
Description based on: February 2008.
Keywords: Small business -- Australia -- Statistics -- Periodicals; Australian